Jo Cox, public feeling and British political culture: #MoreInCommon. (October 2022) - Johnson, Beth; Parry, Katy
Five years after the murder of British MP, Jo Cox, during the European Union referendum campaign in 2016, this article examines the More In Common initiative through two sites of participatory practice: on Twitter via two related hashtags–#MoreInCommon and #LoveLikeJo–and the 'More In Common' exhibition (2021–2022) at the People's History Museum in Manchester. We consider how both spaces help to organise public feeling and consider the ways in which these sites draw on Cox's identity politics and values to curate her political legacy. We identify three emergent logics through our thematic analysis of the tweets posted with the hashtags in the month following her death: connected, visual and resistant. Considering the political legacy of 'more in common' 5 years later, we then trace the movement of the campaign from the digital to the physical and assess the ways in which Cox's values are crystalized through co-created participatory artistic projects displayed in public gallery space.